ФРОЛОВ М.О. КОМПАРТІЙНО-РАДЯНСЬКА ЕЛІТА В УСРР (1917-1922 рр.): СТАНОВЛЕННЯ І ФУНКЦІОНУВАННЯ. – ЗАПОРІЖЖЯ: ПРЕМ’ЄР, 2003. – 448 с. (Zaporizhzhia Historical Review, 2021)
In reviewed book by M. Frolov the problems of formation and function of the soviet communist-party elite in 1917-1922 years in Ukraine are investigated. The object of author’s exploration is the formation of the political elite of the Ukrainian SSR and the main peculiarities of its activity in the conditions of the civil war.